CORONAVIRUS PREVENTION METHODS IN DENTAL PRACTICES - László Tüzes; Dorin Ioan Cocoș; Miklós Szőts; Sorana Maria Bucur (Romanian Society of Oral Rehabilitation, 2022)
The present clinical study aimed to assess requests for dental treatment during the COVID-19 pandemic, examine factors influencing the choice of dental practice during the pandemic, and investigate why patients did not use dental services. Material and method: we used a questionnaire-based survey based on our ideas, distributed on the internet and various social platforms. Results: 106 people, mean age 26.4, completed the survey. The pandemic for those under 45 years old did not significantly influence the behavior regarding the use of dental services (p=0.908). The majority of respondents agreed that before dental treatments every patient should undergo a rapid test. For those who sought dental services only when needed, the difference did not show significant values before and during the pandemic (p=0.825). A statistically significant correlation was found between patients who would change their practice because of the protection conditions, and patients who would be willing to pay more to be provided with infection prevention protection (p≤0.00001). Conclusions: During the pandemic, dental services were especially in emergency cases, and regular check-ups were postponed. The most important things for patients during the pandemic proved to be the professionalism of the medical staff, the respect for hygiene, and the wearing of specific protective equipment. Every patient should be tested for coronavirus before dental intervention.